Principals of Implementing Early Mobilization in Patients in Intensive Care Units - Putri, Safridha Kemala; Noor, Mohammad Arifin; Aini, Dwi Nur; Cahya, Mochamad Robby Fajar; Mahoklory, Serly Sani; Nazara, Desman Serius (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Early mobilization is a series of light activities carried out after surgery starting in bed until being able to get out of bed, mobilize to the bathroom and walk out of the bathroom. Advances in intensive care allow more patients to survive acute critical illness. The use of mechanical ventilation is one of the advances in the care of critically ill patients that can have a negative impact on long-term use. The aim is to provide information about the benefits and application of early mobilization in patients undergoing treatment in the ICU and using mechanical ventilation. Results: early mobilization has an effect on physiological responses, reduces delirium scores, reduces the length of use of mechanical ventilation, reduces length of stay in the ICU and hospital and reduces treatment costs, and prevents VAP. One of the obstacles to early mobilization is the mindset of ICU staff. The conclusion is that early mobilization is one of the items for ICU patients and what hinders its implementation is the mindset of the ICU staff.